Combating Social Isolation and Loneliness in Online Distance Learning: Lived Experiences of College Students - Aira Jessa B. Palisoc; Agne Kryza H. Sito (Philippine Social Science Journal)
The COVID-19 pandemic and the shift to online distance learning (ODL) intensify social isolation and loneliness globally, particularly among college students. This study explores the experiences of nine university students in Baguio City who face these challenges. Through semi-structured interviews and Interpretative Phenomenological Analysis, the research reveals students struggle with their psychological well-being, the emotional impact of ODL, and demanding academic adjustments. However, students also develop coping strategies and seek support, ultimately viewing ODL as an innovative learning environment. These findings highlight the need for educators and policymakers to reassess current practices and implement strategies that support the holistic development of students in the evolving digital landscape.